Low density polyethylene blended with acid copolymer resin for enhanced adhesion to aluminum foil
A polymer blend of LDPE and an acid copolymer addresses the adhesion issues with polar substrates by improving bonding, ensuring strong adhesion and integrity in packaging at high speeds.
Patent Information
- Application Number
- JP2022506191
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-07-31
- Filing Date
- 2020-07-27
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2040-07-27
AI Technical Summary
Low density polyethylene (LDPE) exhibits poor adhesion to polar substrates like aluminum foil and metallized films, leading to package failure and compromised barrier properties in food packaging, especially at medium to high extrusion coating line speeds.
A polymer blend comprising at least 90% LDPE and 1% to 10% of an acid copolymer, with specific melt index and molecular weight distribution, is used to enhance adhesion to polar substrates by incorporating functional groups that improve bonding.
The polymer blend achieves improved peel strength, ensuring effective adhesion to polar substrates even at high line speeds, enhancing the integrity and barrier properties of packaging.
Smart Images

Figure 0007655895000001 
Figure 0007655895000002 
Figure 0007655895000003
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to International Patent Application No. PCT / CN2018 / 098558, filed July 31, 2019, the entire disclosure of which is incorporated herein by reference.
[0002] FIELD OF THE DISCLOSURE Embodiments of the present disclosure generally relate to polymer blends with improved adhesion to metal for extrusion coating or lamination, and to films and coated substrates comprising the polymer blends. [Background technology]
[0003] Low density polyethylene (LDPE) is widely used in extrusion coating to produce food packaging such as condiment bags, potato chip bags, and many flexible packages. However, the poor bond strength of LDPE to polar substrates such as aluminum foil and metallized films can cause the package to fail, impair barrier properties, and potentially spoil the food. Adhesion to polar substrates is promoted by polar functional groups such as carbonyl groups. LDPE is non-polar, so it generally has poor adhesion to foils and metallized films. To improve adhesion, LDPE can be extruded and coated at high temperatures (typically 280-330°C). High temperature extrusion coating can generate carbonyl groups that promote oxidation at the polymer surface and result in better adhesion. In addition to temperature, the level of oxidation is also related to the time the hot polymer is exposed to air before contacting the substrate to be coated. Extrusion coating lines run at line speeds of 100-800 meters per minute (m / min). At higher line speeds, much less oxidation occurs. Less oxidation results in fewer carbonyl groups being formed, reducing the ability of the LDPE coating to adhere to polar substrates. Summary of the Invention [Problem to be solved by the invention]
[0004] There remains a need for polymers or polymer blends that can be processed at medium to high extrusion coating line speeds (eg, 200 m / min to 800 m / min) and that have good adhesion to polar substrates such as aluminum foil.
[0005] An embodiment of the present disclosure includes a polymer blend comprising at least 90% by weight of a low density polyethylene (LDPE) polymer and 1% to 10% by weight of an acid copolymer, based on the total weight of the polymer blend. In the polymer blend, the LDPE polymer has a melt index (I2) of 2 g / 10 min to 8 g / 10 min, as determined according to ASTM D1238 (190° C., 2.16 kg), and a molecular weight distribution (MWD) of 5 to 10.5, as determined by conventional gel permeation chromatography. In the polymer blend, the acid copolymer is the polymerization reaction product of at least 60% by weight of ethylene monomer, based on the total weight of monomers present in the ethylene acid copolymer, 1% to 20% by weight of a monocarboxylic acid monomer, based on the total weight of monomers present in the ethylene acid copolymer, and 0 to 20% by weight of an alkyl acrylate monomer, based on the total weight of monomers present in the ethylene acid copolymer.
[0006] An embodiment of the present disclosure includes a coated metal substrate comprising a metal substrate and a film comprising a polymer blend of any of the polymer blends of the present disclosure adhered to the metal substrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] An embodiment of the present disclosure includes a polymer blend comprising at least 90% by weight of a low density polyethylene (LDPE) polymer and 1% to 10% by weight of an acid copolymer, based on the total weight of the polymer blend.
[0008] In some embodiments of the polymer blend, the LDPE polymer has a viscosity of 1000:1 as determined according to ASTM D1238 (190° C., 2.16 kg). 2g / 10min to 16g / 10min, preferably 2g / 10 minutes~8g / 10 minutes , more preferably 2g / 10min to 5.8g / 10min In various embodiments, the LDPE homopolymer has a melt index (I2) of from 2 g / 10 min to 7.7 g / 10 min, from 2 g / 10 min to 6 g / 10 min, from 2 g / 10 min to 5 g / 10 min, or from 2 g / 10 min to 4.5 g / 10 min.
[0009] In one or more embodiments of the polymer blend, the LDPE polymer has a molecular weight distribution (MWD=Mw / Mn) of 5 to 11, 8 to 10.5, or 8.5 to 11, as determined by conventional gel permeation chromatography (GPC) methods.
[0010] LDPE polymer is Preferably 0.910 g / cc to 0.935 g / cc, more preferably It may have a density of 0.910 g / cc to 0.930 g / cc. In some embodiments, the LDPE polymer may have a density of 0.910 g / cc to 0.920 g / cc, 0.916 g / cc to 0.930 g / cc, 0.918 g / cc to 0.926 g / cc, or 0.915 g / cc to 0.920 g / cc.
[0011] In some embodiments of the polymer blend, the LDPE polymer has a viscosity of 0.910 g / cm 3 ~0.930g / cm 3 and MWD of 8.5 to 10.5.
[0012] In one or more embodiments, the polymer blend comprises between 1% and 10% by weight of the acid copolymer, hi some embodiments, the polymer blend comprises between 2% and 8%, between 3% and 6%, or between 3% and 5% by weight of the acid copolymer.
[0013] In various embodiments of the polymer blend, the acid copolymer is the polymerization reaction product of at least 60% by weight ethylene, based on the total weight of monomers present in the ethylene acid copolymer, from 1% to 20% by weight monocarboxylic acid monomer, based on the total weight of monomers present in the ethylene acid copolymer, and from 0 to 20% by weight alkyl acrylate monomer, based on the total weight of monomers present in the ethylene acid copolymer.
[0014] In one or more embodiments, the monocarboxylic acid monomer of the acid copolymer may be present in the acid copolymer in an amount of from 1% to 15% by weight, based on the total weight of monomers present in the ethylene-based polymer. In some embodiments, the monocarboxylic acid monomer may be present in an amount of from 2% to 20% by weight, from 2% to 10% by weight, or from 2% to 5% by weight, based on the total weight of monomers present in the acid copolymer.
[0015] In some embodiments of the polymer blend, the ethylene acid copolymer comprises at least 65% by weight ethylene monomer, based on the total weight of monomers in the ethylene acid copolymer, 1% to 15% by weight monocarboxylic acid monomer, based on the total weight of monomers in the ethylene acid copolymer, and 0 to 15% by weight alkyl acrylate, based on the total weight of monomers in the ethylene acid copolymer.
[0016] In one or more embodiments, the ethylene acid copolymer comprises at least 75% by weight ethylene, 2% to 6% by weight monocarboxylic acid monomer, based on the total weight of monomers in the ethylene acid copolymer, and 1% to 15% by weight alkyl acrylate, based on the total weight of monomers in the ethylene acid copolymer.
[0017] In various embodiments of the polymer blend, the monocarboxylic acid monomer comprises acrylic acid, methacrylic acid, or a combination thereof.
[0018] In some embodiments of the polymer blend, the alkyl acrylate of the acid copolymer can be, by way of example and not limitation, methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, or combinations thereof. In various embodiments, the alkyl acrylate is a C2-C8 alkyl acrylate, i.e., an alkyl acrylate having an alkyl group containing from 1 to 8 carbons.
[0019] In one or more embodiments of the polymer blend, the acid copolymer has a melt index (I2) determined according to ASTM D1238 (190° C., 2.16 kg) of 2 g / 10 min to 30 g / 10 min. In some embodiments, the acid copolymer has a melt index (I2) of 10 g / 10 min to 30 g / 10 min.
[0020] In one or more embodiments of the present disclosure, the polymer blend includes, in addition to the LDPE polymer and the acid copolymer, a linear low density polyethylene (LLDPE) polymer. In one or more embodiments, the LLDPE polymer has a melt index (I2) of 0.5 g / 10 min to 30 g / 10 min, as determined according to ASTM D1238 (190° C., 2.16 kg), and 0.910g / cm 3 ~0.935g / cm 3 , preferably 0.910g / cm 3 ~0.925g / cm 3 has a density of
[0021] In one or more embodiments of the polymer blend, the ethylene acid copolymer has a melt index (I2) from 2 g / 10 min to 12 g / 10 min as determined according to ASTM D1238 (190° C., 2.16 kg). Melt index (I) of 0.5 g / 10 min to 30 g / 10 min as determined according to ASTM D1238 (190 °C, 2.16 kg) 2 ), wherein the ethylene copolymer has at least 50% by weight of ethylene, based on the total weight of monomers present in the ethylene copolymer; Also provided is a polymer blend comprising the reaction product of from 0.1% to 40% by weight of a comonomer, based on the total weight of monomers present in the ethylene copolymer, wherein the comonomer is selected from vinyl acetate, acrylate, or carboxylic acid comonomers.
[0022] An embodiment of the present disclosure includes a coating, the coating comprising a polymer blend of the present disclosure.
[0023] Embodiments of the present disclosure include a coated substrate. In some embodiments, the coated substrate is a coated polymeric substrate. The coated polymeric substrate includes a polymeric substrate and a coating on the polymeric substrate comprising any of the polymeric blends of the present disclosure.
[0024] In one or more embodiments of the coated polymeric substrate, the polymeric substrate comprises polyethylene, polypropylene, polyethylene terephthalate, or polyamide. In some embodiments, the polymeric substrate is uniaxially or biaxially oriented.
[0025] In some embodiments, the coated substrate comprises a coated metal substrate. The coated metal substrate comprises a metal substrate and a coating on the metal substrate. The coating comprises any of the polymer blends of the present disclosure.
[0026] In some embodiments, the metal substrate comprises aluminum or a metallized polymer substrate, and the coating is adhered to the metallized surface of the metallized polymer substrate. In one or more embodiments, the polymer substrate is polyethylene terephthalate (PET), polyethylene, polypropylene, or polyamide.
[0027] Embodiments of the present disclosure include a multi-layer structure, in some embodiments, the multi-layer structure includes a second substrate in contact with the coating of the coated substrate.
[0028] In one or more embodiments, the coating has a peel strength of at least 0.6 N / in, at least 0.7 N / in, at least 1 N / in, or at least 2 N / in, as measured by ASTM F904.
[0029] polymerization Two basic types of reactors are known for high pressure free radical initiated polymerization processes. The first type is a stirred autoclave vessel with one or more reaction zones (autoclave reactor). The second type is a jacketed tube with one or more reaction zones (tubular reactor).
[0030] The pressure in each autoclave and tubular reactor zone of the process is typically from 100 MPa to 400 MPa, from 120 MPa to 360 MPa, or from 150 MPa to 320 MPa.
[0031] The polymerization temperature in each tubular reactor zone of the process is typically from 100°C to 400°C, from 130°C to 360°C, or from 140°C to 330°C.
[0032] The polymerization temperature in each autoclave reactor zone of the process is typically from 150°C to 300°C, from 165°C to 290°C, or from 180°C to 280°C.
[0033] To produce the LDPE polymer blend, a tubular reactor having at least three reaction zones can be used.
[0034] To produce LDPE, a high pressure, free radical initiated polymerization process is typically used. Typically, a jacketed tube is used as the reactor, which has one or more reaction zones. Suitable, but not limited to, reactor lengths can be 100 to 3000 meters (m) or 1000 to 2000 meters. The beginning of the reactor reaction zone is typically defined by the side injection of the initiator of the reaction, ethylene, the chain transfer agent (or telogen), and any combination of these. The high pressure process can be carried out in one or more tubular reactors with one or more reaction zones, or a combination of autoclaves and tubular reactors, each containing one or more reaction zones.
[0035] Chain transfer agents can be used to control molecular weight. In a preferred embodiment, one or more chain transfer agents (CTAs) are added to the process of the present invention. Typical CTAs that can be used include, but are not limited to, propylene, n-butane, 1-butene, isobutane, propionaldehyde, and methyl ethyl ketone. In one embodiment, the amount of CTA used in the process is 0.03-10% by weight of the total reaction mixture. The ethylene used for the production of LDPE can be purified ethylene, obtained by removing polar components from a loop recycle stream or by using a reaction system configuration such that only fresh ethylene is used to make the polymer of the present invention. It is not typical that only purified ethylene is required to make an ethylene-based polymer. In such cases, ethylene from the recycle loop may be used. In one embodiment, the ethylene-based polymer is an LDPE.
[0036] Ethylene acid copolymers can be prepared by standard free radical copolymerization methods using high pressure and operating continuously. Monomers are fed to the reaction mixture in a constant ratio relative to the activity of the monomer and the amount of monomer desired to be incorporated into the copolymer. In this way, a uniform, nearly random distribution of monomer units along the chain is achieved. Unreacted monomers can be recycled. Additional information on the preparation of ethylene acid copolymers can be found in U.S. Pat. Nos. 3,264,272 and 4,766,174, each of which is incorporated herein by reference in its entirety.
[0037] Initiator The process for producing the LDPE of the polymer blend of the present disclosure is a free radical polymerization process. The type of free radical initiator used in the process is not critical, but preferably one of the initiators applied should allow high temperature operation in the range of 300°C to 350°C. Examples of suitable free radical initiators include organic peroxides such as peresters, perketals, peroxyketones, percarbonates, and cyclic polyfunctional peroxides. These organic peroxy initiators are added to the reactor at 0.005% to 0.2% by weight based on the total weight of the polymerizable monomers in the reactor. The peroxide is typically injected as a dilute solution in a suitable solvent, for example a hydrocarbon solvent.
[0038] Other suitable initiators include azodicarboxylic acid esters, azodicarboxylic acid dinitriles, and 1,1,2,2-tetramethylethane derivatives, as well as other components capable of forming free radicals in the desired operating temperature range.
[0039] In one embodiment, the initiator is added to at least one reaction zone of the polymerization reactor. In a further embodiment, the initiator is added to the reactor or polymerization process at a peak polymerization temperature of 320° C. to 350° C. In a further embodiment, the initiator includes at least one peroxide group incorporated into a cyclic structure.
[0040] Examples of suitable initiators for the polymerization of polyethylene include, but are not limited to, TRIGONOX 301 (3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxonane) and TRIGONOX 311 (3,3,5,7,7-pentamethyl-1,2,4-trioxepane), both available from Akzo Nobel, and HMCH-4-AL (3,3,6,6,9,9-hexamethyl-1,2,4,5-tetroxonane), available from United Initiators. Additional initiators are disclosed in WO 02 / 14379 and WO 01 / 68723, both of which are incorporated herein by reference.
[0041] Polymer Production The polymer blends of the present disclosure can be used in a variety of thermoplastic manufacturing processes, including extrusion coating and extrusion lamination, to produce useful articles.
[0042] definition Unless stated to the contrary, implicit from the context, or customary in the art, all parts and percentages are by weight and all testing methods are current as of the filing date of this disclosure.
[0043] The term "blend" or "polymer blend" as used in this disclosure means an intimate physical mixture of two or more polymers without polymer-polymer or interpolymer chemical reactions. A blend may be miscible and free of phase separation at the molecular level, or immiscible and may exhibit some degree of phase separation at the molecular level. A blend may, but need not, include one or more domain configurations, which can be determined from transmission electron spectroscopy, light scattering, X-ray scattering, and other methods known in the art. A blend may be affected by physically mixing two or more polymers at the macro or micro level. Examples of physical mixing at the macro level include melt blending or compounding of resins. Examples of physical mixing at the micro level include the simultaneous formation of two or more polymers in the same reactor.
[0044] The term "polymer" refers to a polymeric compound prepared by polymerizing monomers, whether the monomers are of the same or different types. Thus, the generic term polymer encompasses the terms "homopolymer" and "copolymer." The term "homopolymer" refers to a polymer prepared from only one type of monomer, while the term "copolymer" refers to a polymer prepared from two or more different monomers.
[0045] The terms "ethylene-based polymer" or "ethylene polymer" refer to a polymer that contains at least 50 weight percent polymerized ethylene, based on the total weight of the polymer. Ethylene-based polymers and ethylene polymers can be ethylene homopolymers or can contain one or more comonomers, provided that ethylene has the largest weight fraction of the polymer among all monomers in the polymer.
[0046] The term "monocarboxylic acid monomer" means a molecule that has a reactive moiety, such as vinyl or vinylene, that can combine with other monomers to form a carboxylic acid (-C(O)OH) moiety that is not included in the polymer and is not a reactive moiety.
[0047] Test Method Density: Samples for density measurement are prepared according to ASTM D 1928. The polymer sample is pressed at 190° C. and 30,000 psi for 3 minutes, then at 21° C. and 207 MPa for 1 minute. Measurements are made within 1 hour of pressing the sample using ASTM D792, Method B.
[0048] Melt Index: Melt index, or I2, (grams / 10 minutes or dg / min), is measured in accordance with ASTM D 1238, Condition 190° C. / 2.16 kg, Method B.
[0049] Triple detector gel permeation chromatography (3D-GPC) The chromatography system includes a PolymerChar GPC-IR (Valencia, Spain) high temperature GPC chromatograph with an internal IR5 infrared detector (IR5) coupled to a Precision Detectors (now Agilent Technologies) two-angle laser light scattering (LS) detector model 2040. For all light scattering measurements, a 15 degree angle is used for measurement purposes. The autosampler oven compartment is set to 160°C and the column compartment is set to 150°C. The columns available include four Agilent "Mixed A" 30 cm, 20 micron linear mixed bed columns. The chromatography solvents available include 1,2,4 trichlorobenzene containing 200 ppm butylated hydroxytoluene (BHT). The solvent source is nitrogen injected. The injection volumes available include 200 microliters (μL) and the flow rate was 1.0 milliliters / min.
[0050] Calibration of the GPC column set is performed with at least 20 narrow molecular weight distribution polystyrene standards with molecular weights ranging from 580 to 8,400,000, arranged in six "cocktail" mixtures spaced at least one decade apart, meaning that there are approximately 10 orders of magnitude between the individual molecular weights. Standards are purchased from Agilent Technologies. Polystyrene standards are prepared at 0.025 grams in 50 milliliters of solvent for molecular weights equal to or greater than 1,000,000, and 0.05 grams in 50 milliliters of solvent for molecular weights less than 1,000,000. The polystyrene standards were dissolved at 80° C. with gentle agitation for 30 minutes. The polystyrene standard peak molecular weights are converted to polyethylene molecular weights using the following formula 1 (as described in Williams and Ward, J. Polym. Sci., Polym. Let., 6, 621 (1968)): M ポリエチレン =A×(M ポリスチレン ) B (Formula 1) where M is the molecular weight, A has a value of 0.4315, and B is equal to 1.0.
[0051] Use a fifth order polynomial to fit each of the polyethylene equivalent calibration points. Make a small adjustment to A (approximately 0.415 to 0.44) to correct for column resolution and band broadening effects so that the NIST standard NBS 1475 is obtained at 52,000 g / mol (Mw).
[0052] Total plate counts for the GPC column set were performed with Eicosane (prepared at 0.04 g in 50 milliliters of TCB and dissolved for 20 minutes with gentle agitation). Plate counts (Equation 2) and symmetry (Equation 3) are measured with a 200 microliter injection according to the following formula:
number
number
[0053] Samples were prepared semi-automatically using PolymerChar "Instrument Control" software to achieve a target sample weight of 2 mg / mL, and solvent (containing 200 ppm BHT) was added via the PolymerChar high temperature autosampler to a septa-capped vial that had been pre-flushed with nitrogen. Samples were dissolved at 160 degrees Celsius with "slow" shaking for 2 hours.
[0054] Mn(GPC) , Mw (GPC) , and Mz (GPC) The calculations are based on GPC results obtained using the internal IR5 detector (measurement channel) of a PolymerChar GPC-IR chromatograph according to Equations 4-6 using PolymerChar GPCOne™ software, baseline-subtracted IR chromatograms at each equally spaced data collection point (i), and the polyethylene equivalent molecular weights obtained from a narrow standard calibration curve for point (i) from Equation 1.
number
number
number
[0055] To monitor deviations over time, a flow marker (decane) is introduced into each sample via a micropump controlled by the PolymerChar GPC-IR system. This flow marker (FM) is aligned with the respective decane peak (RV) in the sample. (FM試料) ) to narrow standard calibration (RV (FM較正済み) The pump flow rate (flow rate) of each sample was calculated by matching the RV with the decane peak in the (見かけ) ) was used to linearly calibrate the flow rate (flow (有効) ) is assumed to be related to a linear shift in the apparent flow rate. To facilitate the highest accuracy of the RV measurement of the flow marker peaks, the peaks of the flow marker concentration chromatogram are fitted to a quadratic equation using a least squares fitting routine. The first derivative of the quadratic equation is used to determine the true peak position. After calibrating the system based on the flow marker peaks, the effective flow rate (for a narrow standard calibration) is calculated as in Equation 7. Processing of the flow marker peaks was performed with PolymerChar GPCOne™ software. An acceptable flow correction should be that the effective flow rate is within + / - 2% of the apparent flow rate. flow rate (有効) =Flow rate (見かけ) ×(RV (FM較正済み) / RV (FM試料) ) (Equation 7)
[0056] A systematic approach for the determination of multiple detector offsets was performed in a manner consistent with that published by Balke, Mourey et al. (Mourey and Balke, Chromatography Polym. Chpt 12, (1992)) (Balke, Thitiratsakul, Lew, Cheung, Mourey, Chromatography Polym. Chpt 13, (1992)) using PolymerChar GPCOne™ software to optimize triple detector log (MW and IV) results from broad homopolymer polyethylene standards (Mw / Mn>3) against narrow standard column calibration results from narrow standard calibration curves.
[0057] Extrusion Coating: Extrusion coating trials are performed using a Black-Clawson line following standard coating procedures. Briefly, a single layer coating is extruded using a three-layer extrusion coating (EC) line using only a 3.5-inch diameter primary extruder (30:1 L / D) equipped with a 150 HP Eurotherm drive. The primary barrel has six heater zones with a temperature profile of 179°C, 230°C, 286°C, 316°C, 317°C, 318°C (354°F, 446°F, 546°F, 601°F, 603°F, 605°F). A Nordson EDI 36-inch Autoflex™ die is used, set with a die gap of 0.5-0.6 mm (0.020 in.) and an air gap of 153 mm (6 in.). The line is equipped with a 30-inch chill roll, nip roll, backing roll, and shear slitter.
[0058] Extrusion coating runs were performed at 600°F (315°C) with 25 gsm, 90 RPM screw speed, 250 lbs / hr, 24 inch die width, 20 mil die gap, resulting in a coating thickness of 1.2 mils (30 microns) at 440 ft / min.
[0059] Peel strength measured in a peel test The polymer or polymer blend is extrusion coated onto an aluminum sheet (aluminum foil laminated with LDPE and white paper, with a total thickness of 5.2-5.5 mils) via an extrusion coating process. The coating is applied to the aluminum side and has a thickness of 1.2 mils. Masking tape is placed on a portion of the aluminum sheet before the polymer or polymer blend is extruded and coated onto the aluminum sheet. Because the adhesion between the masking tape and the coating is weak, the masking tape can be peeled off from the coating before the peel test. A peel test is then used to obtain the peel strength between the coating and the aluminum sheet.
[0060] Prior to testing for peel strength, samples are conditioned at 23° C. (±2° C.) and 50% (±10%) relative humidity (RH) for a minimum of 40 hours.
[0061] The extrusion coated sheet to be tested was cut into 1 inch wide strips along the machine direction with the long edge oriented along the machine direction. The coating was peeled from the aluminum sheet (from where the masking tape was) and then the two jaws of the tensile tester gripped the edge of the peeled coating and aluminum sheet. The entire sample was then slowly pulled at 1 in / min to remove the slack. The sample was then tested at 12 in / min, with five specimens tested and the average peak load and average peak load over 3 inches (1 in - 4 in) reported.
[0062] The improvement in peel strength (%) is given by the following formula:
number
[0063] The peel strength is the peak load obtained from the peel test. EXAMPLES
[0064] Twenty-five example compositions were prepared and the polymer properties of each were measured. Each of the example compositions was a blend of LDPE homopolymer and an acid copolymer. The properties of the LDPE homopolymer are shown in Table 1. [Table 1]
[0065] Example 1 was a polymer blend prepared from 95 wt% AGILITY™ EC 7030 and 5 wt% acid copolymer manufactured by Dow, Inc. as the LDPE component. The acid copolymer contained 2 wt% methacrylic acid, 6 wt% isobutyl acrylate, and 92 wt% ethylene, based on the total weight of the monomers of the acid copolymer, and had a melt index of 10 dg / min. Example 2 was a polymer blend prepared from 95 wt% AGILITY™ EC 7030 and 5 wt% acid copolymer manufactured by Dow, Inc. as the LDPE component. The acid copolymer contained 10 wt% methacrylic acid, 10 wt% isobutyl acrylate, and 80 wt% ethylene, based on the total weight of the monomers of the acid copolymer, and had a melt index of 10 dg / min.
[0066] Example 3 was a polymer blend prepared from 95 wt. % AGILITY™ EC 7030 manufactured by Dow, Inc. as the LDPE component, and 5 wt. % acid copolymer. The acid copolymer contained 9 wt. % methacrylic acid, and 91 wt. % ethylene, based on the total weight of the monomers in the acid copolymer, and had a melt index of 10 dg / min.
[0067] Example 4 was a polymer blend prepared from 95 wt. % AGILITY™ EC 7000 manufactured by Dow, Inc. as the LDPE component, and 5 wt. % acid copolymer. The acid copolymer contained 9 wt. % methacrylic acid and 91 wt. % ethylene, based on the total weight of the monomers in the acid copolymer, and had a melt index of 10 dg / min.
[0068] Example 5 was a polymer blend prepared from 95 wt. % AGILITY™ EC 7000 manufactured by Dow, Inc. as the LDPE component, and 5 wt. % acid copolymer. The acid copolymer contained 2 wt. % methacrylic acid, and 6 wt. % isobutyl acrylate, and 92 wt. % ethylene, based on the total weight of the monomers in the acid copolymer, and had a melt index of 10 dg / min.
[0069] Example 6 was a polymer blend prepared from 95 wt. % LDPE 5005 manufactured by Dow, Inc. as the LDPE component, and 5 wt. % acid copolymer. The acid copolymer contained 2 wt. % methacrylic acid, and 6 wt. % isobutyl acrylate, and 92 wt. % ethylene, based on the total weight of the monomers in the acid copolymer, and had a melt index of 10 dg / min.
[0070] Example 7 was a polymer blend prepared from 95 wt. % LDPE PG 7008 manufactured by Dow, Inc. as the LDPE component, and 5 wt. % acid copolymer. The acid copolymer contained 2 wt. % methacrylic acid, and 6 wt. % isobutyl acrylate, and 92 wt. % ethylene, based on the total weight of the monomers in the acid copolymer, and had a melt index of 10 dg / min.
[0071] Example 8 was a polymer blend prepared from 95 wt. % LDPE 4016 manufactured by Dow, Inc. as the LDPE component, and 5 wt. % acid copolymer. The acid copolymer contained 2 wt. % methacrylic acid, and 6 wt. % isobutyl acrylate, and 92 wt. % ethylene, based on the total weight of the monomers in the acid copolymer, and had a melt index of 10 dg / min.
[0072] Example 9 was a polymer blend prepared from 95 wt. % LDPE 621I manufactured by Dow, Inc. as the LDPE component, and 5 wt. % acid copolymer. The acid copolymer contained 2 wt. % methacrylic acid, and 6 wt. % isobutyl acrylate, and 92 wt. % ethylene, based on the total weight of the monomers in the acid copolymer, and had a melt index of 10 dg / min.
[0073] Example 10 was a polymer blend prepared from 95 wt. % LDPE 722 manufactured by Dow, Inc. as the LDPE component, and 5 wt. % acid copolymer. The acid copolymer contained 2 wt. % methacrylic acid, and 6 wt. % isobutyl acrylate, and 92 wt. % ethylene, based on the total weight of the monomers in the acid copolymer, and had a melt index of 10 dg / min.
[0074] Example 11 was a polymer blend prepared from 95 wt. % LDPE 4010 manufactured by Dow, Inc. as the LDPE component, and 5 wt. % acid copolymer. The acid copolymer contained 2 wt. % methacrylic acid, and 6 wt. % isobutyl acrylate, and 92 wt. % ethylene, based on the total weight of the monomers in the acid copolymer, and had a melt index of 10 dg / min.
[0075] Example 12 was a polymer blend prepared from 95 wt. % LDPE 621I manufactured by Dow, Inc. as the LDPE component, and 5 wt. % acid copolymer. The acid copolymer contained 9 wt. % methacrylic acid, and 91 wt. % ethylene, based on the total weight of the monomers in the acid copolymer, and had a melt index of 10 dg / min.
[0076] Example 13 was a polymer blend prepared from 95 wt. % LDPE 5005 manufactured by Dow, Inc. as the LDPE component, and 5 wt. % acid copolymer. The acid copolymer contained 9 wt. % methacrylic acid, and 91 wt. % ethylene, based on the total weight of the monomers in the acid copolymer, and had a melt index of 10 dg / min.
[0077] Example 14 was a polymer blend prepared from 95 wt. % LDPE 722 manufactured by Dow, Inc. as the LDPE component, and 5 wt. % acid copolymer. The acid copolymer contained 9 wt. % methacrylic acid, and 91 wt. % ethylene, based on the total weight of the monomers in the acid copolymer, and had a melt index of 10 dg / min.
[0078] Example 15 was a polymer blend prepared from 95 wt. % LDPE PG 7008 manufactured by Dow, Inc. as the LDPE component, and 5 wt. % acid copolymer. The acid copolymer contained 9 wt. % methacrylic acid, and 91 wt. % ethylene, based on the total weight of the monomers in the acid copolymer, and had a melt index of 10 dg / min.
[0079] Example 16 was a polymer blend prepared from 95 wt. % LDPE 4010 manufactured by Dow, Inc. as the LDPE component, and 5 wt. % acid copolymer. The acid copolymer contained 9 wt. % methacrylic acid, and 91 wt. % ethylene, based on the total weight of the monomers in the acid copolymer, and had a melt index of 10 dg / min.
[0080] Example 17 was a polymer blend prepared from 95 wt. % LDPE 4016 manufactured by Dow, Inc. as the LDPE component, and 5 wt. % acid copolymer. The acid copolymer contained 9 wt. % methacrylic acid, and 91 wt. % ethylene, based on the total weight of the monomers in the acid copolymer, and had a melt index of 10 dg / min.
[0081] Example 18 was a polymer blend prepared from 95 wt. % LDPE 621I manufactured by Dow, Inc. as the LDPE component, and 5 wt. % acid copolymer. The acid copolymer contained 10 wt. % methacrylic acid, and 10 wt. % isobutyl acrylate, and 80 wt. % ethylene, based on the total weight of the monomers in the acid copolymer, and had a melt index of 10 dg / min.
[0082] Example 19 was a polymer blend prepared from 95 wt. % LDPE 5005 manufactured by Dow, Inc. as the LDPE component, and 5 wt. % acid copolymer. The acid copolymer contained 10 wt. % methacrylic acid, and 10 wt. % isobutyl acrylate, and 80 wt. % ethylene, based on the total weight of the monomers in the acid copolymer, and had a melt index of 10 dg / min.
[0083] Example 20 was a polymer blend prepared from 95 wt. % LDPE 722 manufactured by Dow, Inc. as the LDPE component, and 5 wt. % acid copolymer. The acid copolymer contained 10 wt. % methacrylic acid, and 10 wt. % isobutyl acrylate, and 80 wt. % ethylene, based on the total weight of the monomers in the acid copolymer, and had a melt index of 10 dg / min.
[0084] Example 21 was a polymer blend prepared from 95 wt. % LDPE PG 7008 manufactured by Dow, Inc. as the LDPE component, and 5 wt. % acid copolymer. The acid copolymer contained 10 wt. % methacrylic acid, and 10 wt. % isobutyl acrylate, and 80 wt. % ethylene, based on the total weight of the monomers in the acid copolymer, and had a melt index of 10 dg / min.
[0085] Example 22 was a polymer blend prepared from 95 wt. % LDPE 4010 manufactured by Dow, Inc. as the LDPE component, and 5 wt. % acid copolymer. The acid copolymer contained 10 wt. % methacrylic acid, and 10 wt. % isobutyl acrylate, and 80 wt. % ethylene, based on the total weight of the monomers in the acid copolymer, and had a melt index of 10 dg / min.
[0086] Example 23 was a polymer blend prepared from 95 wt. % LDPE 4016 manufactured by Dow, Inc. as the LDPE component, and 5 wt. % acid copolymer. The acid copolymer contained 10 wt. % methacrylic acid, and 10 wt. % isobutyl acrylate, and 80 wt. % ethylene, based on the total weight of the monomers in the acid copolymer, and had a melt index of 10 dg / min.
[0087] Example 24 was a polymer blend prepared from 97 wt. % AGILITY™ EC 7030 manufactured by Dow, Inc. as the LDPE component, and 3 wt. % acid copolymer. The acid copolymer contained 4 wt. % methacrylic acid, and 15 wt. % isobutyl acrylate, and 81 wt. % ethylene, based on the total weight of the monomers in the acid copolymer, and had a melt index of 27 dg / 10 min.
[0088] Example 25 was a polymer blend prepared from 97 wt. % AGILITY™ EC 7000 manufactured by Dow, Inc. as the LDPE component, and 3 wt. % acid copolymer. The acid copolymer contained 4 wt. % methacrylic acid, and 15 wt. % isobutyl acrylate, and 81 wt. % ethylene, based on the total weight of the monomers in the acid copolymer, and had a melt index of 27 dg / 10 min.
[0089] The properties of each of the polymer blends and the comparative polymers are summarized in Table 2. [Table 2-1] [Table 2-2]
[0090] The addition of 5 wt% of the acid copolymer to the LDPE polymer resulted in a polymer blend with higher peel strength than the LDPE polymer. The invention as originally claimed in the present application is set forth below. [1] A polymer blend comprising: At least 90 wt. % low density polyethylene (LDPE) polymer, based on the total weight of the polymer blend, having a melt index (I ) of 2 g / 10 min to 16 g / 10 min, as determined according to ASTM D1238 (190° C., 2.16 kg). 2 ), and a molecular weight distribution (MWD) of 5 to 10.5 as determined by conventional gel permeation chromatography; and 1 wt % to 10 wt % of an acid copolymer based on the total weight of the polymer blend, the acid copolymer comprising: at least 60% by weight of ethylene, based on the total weight of monomers present in the ethylene acid copolymer; from 1% by weight to 20% by weight of a monocarboxylic acid monomer, based on the total weight of monomers present in the ethylene acid copolymer; and 0 to 20 weight percent of an alkyl acrylate monomer, based on the total weight of monomers present in said ethylene acid copolymer. [2] The LDPE polymer has a viscosity of 0.910 g / cm 3 ~0.935g / cm 3 and MWD of 8.5 to 10.5. [3] The polymer blend according to [1] or [2], wherein the melt index of the LDPE polymer is from 2 g / 10 min to 5.8 g / 10 min, as determined according to ASTM D1238 (190° C., 2.16 kg). [4] The polymer blend according to any one of [1] to [3], wherein the melt index of the LDPE polymer is from 2 g / 10 min to 4.5 g / 10 min, as determined according to ASTM D1238 (190° C., 2.16 kg). [5] Melt index (I) of 0.5 g / 10 min to 30 g / 10 min when determined according to ASTM D1238 (190 °C, 2.16 kg) 2 ), and 0.910 g / cm 3 ~0.935g / cm 3 The polymer blend according to any one of [1] to [4], further comprising a linear low density polyethylene (LLDPE) polymer having a density of [6] Melt index (I) of 0.5 g / 10 min to 30 g / 10 min when determined according to ASTM D1238 (190 °C, 2.16 kg) 2 ), wherein the ethylene copolymer has at least 50% by weight of ethylene, based on the total weight of monomers present in the ethylene acid copolymer; and 0.1 wt% to 40 wt% of a comonomer, based on the total weight of monomers present in the ethylene copolymer, wherein the comonomer is selected from vinyl acetate, acrylate, or carboxylic acid comonomer. [7] The polymer blend according to any one of [1] to [6], wherein the polymer blend contains 2 wt % to 6 wt % of an acid copolymer, based on the total weight of the polymer blend. [8] The polymer blend according to any one of [1] to [7], wherein the polymer blend comprises 2 wt% to 6 wt% of an acid copolymer, based on the total weight of the polymer blend. [9] The acid copolymer has a melt index (I ) of 2 g / 10 min to 30 g / 10 min as determined in accordance with ASTM 1238 (190° C., 2.16 kg). 2 ) . The polymer blend according to any one of [1] to [8].
[10] The polymer blend according to any one of [1] to [9], wherein the alkyl acrylate monomer comprises methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, or a combination thereof, and the monocarboxylic acid monomer comprises acrylic acid, methacrylic acid, or a combination thereof.
[11] The polymer blend of any of [1] to
[10] , wherein the ethylene acid copolymer comprises at least 65 wt. % ethylene monomer, based on the total weight of monomers in the ethylene acid copolymer, 1 wt. % to 15 wt. % monocarboxylic acid monomer, based on the total weight of monomers in the ethylene acid copolymer, and 0 to 15 wt. % alkyl acrylate, based on the total weight of monomers in the ethylene acid copolymer.
[12] The polymer blend of any of [1] to
[11] , wherein the ethylene acid copolymer comprises at least 75 wt. % ethylene monomer, based on the total weight of monomers in the ethylene acid copolymer, 2 wt. % to 6 wt. % monocarboxylic acid monomer, based on the total weight of monomers in the ethylene acid copolymer, and 1 wt. % to 15 wt. % alkyl acrylate, based on the total weight of monomers in the ethylene acid copolymer.
[13] A coated metal substrate, comprising: A metal substrate; and a coating adhered to the metal substrate, the coating comprising the polymer blend according to any one of [1] to
[12] .
[14] The coated metal substrate of
[13] , wherein the metal substrate comprises aluminum.
[15] The coated metal substrate of
[13] or
[14] , wherein the coating has a peel strength of at least 0.6 N / in as measured by ASTM 904.
[16] The coated metal substrate of
[13] or
[14] , wherein the coating has a peel strength of at least 1 N / in as measured by ASTM F904.
[17] The coated metal substrate of
[13] or
[14] , wherein the coating has a peel strength of at least 2 N / in as measured by ASTM F904.
[18] An extruded article comprising the polymer blend according to any one of [1] to
[12] .
Claims
1. 1. A polymer blend comprising: At least 90 wt. % low density polyethylene (LDPE) polymer, based on the total weight of the polymer blend, having a melt index (I) of 2 g / 10 min to 5.8 g / 10 min, as determined according to ASTM D1238 (190° C., 2.16 kg). 2 ), and a molecular weight distribution (MWD) of 5 to 10.5 as determined by conventional gel permeation chromatography; and 1 wt % to 10 wt % of an ethylene acid copolymer, based on the total weight of the polymer blend, wherein the ethylene acid copolymer is at least 60 weight percent ethylene, based on the total weight of monomers present in the ethylene acid copolymer; from 1% to 20% by weight of a monocarboxylic acid monomer, based on the total weight of monomers present in the ethylene acid copolymer; and 0 to 20 weight percent of an alkyl acrylate monomer, based on the total weight of monomers present in said ethylene acid copolymer.
2. The LDPE polymer has a viscosity of 0.910 g / cm 3 ~0.935g / cm 3 2. The polymer blend of claim 1 having a density of from about 100 to about 150 and a MWD of from about 8.5 to about 10.
5.
3. 2. The polymer blend of claim 1, wherein the melt index of the LDPE polymer is from 2 g / 10 min to 4.5 g / 10 min as determined according to ASTM D1238 (190° C., 2.16 kg).
4. Melt index (I) of 0.5 g / 10 min to 30 g / 10 min as determined according to ASTM D1238 (190° C., 2.16 kg) 2 ), and 0.910 g / cm 3 ~0.935g / cm 3 10. The polymer blend of claim 1, further comprising a linear low density polyethylene (LLDPE) polymer having a density of
5. Melt index (I) of 0.5 g / 10 min to 30 g / 10 min as determined according to ASTM D1238 (190° C., 2.16 kg) 2 ), wherein the ethylene copolymer has at least 50 weight percent ethylene, based on the total weight of monomers present in the ethylene copolymer; 2. The polymer blend of claim 1, comprising the reaction product of from 0.1% to 40% by weight of a comonomer, based on the total weight of monomers present in the ethylene copolymer, wherein the comonomer is selected from vinyl acetate, acrylate, or carboxylic acid comonomer.
6. 10. The polymer blend of claim 1, wherein the polymer blend comprises from 2% to 6% by weight of the ethylene acid copolymer, based on the total weight of the polymer blend.
7. The ethylene acid copolymer has a melt index (I ) of 2 g / 10 min to 30 g / 10 min as determined according to ASTM D1238 (190° C., 2.16 kg). 2 2. The polymer blend of claim 1 having a molecular weight of 1:1 or more.
8. 2. The polymer blend of claim 1, wherein the alkyl acrylate monomer comprises methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, or a combination thereof, and the monocarboxylic acid monomer comprises acrylic acid, methacrylic acid, or a combination thereof.
9. 2. The polymer blend of claim 1, wherein the ethylene acid copolymer comprises at least 65 weight percent ethylene monomer, based on the total weight of monomers in the ethylene acid copolymer, 1 weight percent to 15 weight percent monocarboxylic acid monomer, based on the total weight of monomers in the ethylene acid copolymer, and 0 to 15 weight percent alkyl acrylate, based on the total weight of monomers in the ethylene acid copolymer.
10. 2. The polymer blend of claim 1, wherein the ethylene acid copolymer comprises at least 75% by weight ethylene monomer, based on the total weight of monomers in the ethylene acid copolymer, 2 to 6% by weight monocarboxylic acid monomer, based on the total weight of monomers in the ethylene acid copolymer, and 1 to 15% by weight alkyl acrylate, based on the total weight of monomers in the ethylene acid copolymer.
11. A coated metal substrate comprising: A metal substrate; and a coating comprising the polymer blend of any one of claims 1 to 10 adhered to the metal substrate.
12. The coated metal substrate of claim 11 , wherein the metal substrate comprises aluminum.
13. 12. The coated metal substrate of claim 11, wherein the coating has a peel strength of at least 0.6 N / in as measured by ASTM F904.
14. 12. The coated metal substrate of claim 11, wherein the coating has a peel strength of at least 1 N / in as measured by ASTM F904.
15. 12. The coated metal substrate of claim 11, wherein the coating has a peel strength of at least 2 N / in as measured by ASTM F904.
16. 13. An extruded article comprising the polymer blend of claim 1.
Citation Information
Patent Citations
Polyethylene composition and film obtained therefrom
JP1986266446A
Polyolefin composition
JP1987174245A
Hydrophlic resin composition
JP1992298549A
Moderate density ethylene polymers, process for making the polymers and use in the process with a carbonyl group-containing chain transfer agent
JP2002500250A
Low-acid ethylene copolymers for improved bonding of ldpe to aluminum foil in extrusion coating
JP2004510871A